2017
DOI: 10.18357/ijcyfs82201717758
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive School Experiences and School Ses on Depressive Symptoms in Chinese Children: A Multilevel Investigation

Abstract: Abstract:The current study investigates the effects of teacher support, school connectedness, and school socioeconomic status (SES) on youth depressive symptoms. Data were collected from a sample of 881 students in Grade 6 from 10 primary schools in Northwest China. Hierarchical linear modeling indicated that higher levels of teacher support, school connectedness, and school SES were significantly associated with fewer depressive symptoms. Further, the relationships between school-level SES and youth depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
6
2
1
Order By: Relevance
“…Results indicated that teacher support was not as strong in reducing students' depressive symptoms for low SES schools compared to high SES schools. Cemalcilar (2010) and Yue (2017) examined concepts related to teacher support (satisfaction with teacher-student relationships) and school belonging (depression) but not those factors specifically. This highlights the need for the current study to examine whether Cemalcilar's (2010) and Yue's (2017) results extend to perceived teacher support and sense of school belonging, which, if so, would result in the association between perceived teacher support and sense of school belonging being stronger for students of a high SES compared to students of a low SES.…”
Section: Socioeconomic Status On the Relationship Between Teacher Sup...mentioning
confidence: 99%
See 3 more Smart Citations
“…Results indicated that teacher support was not as strong in reducing students' depressive symptoms for low SES schools compared to high SES schools. Cemalcilar (2010) and Yue (2017) examined concepts related to teacher support (satisfaction with teacher-student relationships) and school belonging (depression) but not those factors specifically. This highlights the need for the current study to examine whether Cemalcilar's (2010) and Yue's (2017) results extend to perceived teacher support and sense of school belonging, which, if so, would result in the association between perceived teacher support and sense of school belonging being stronger for students of a high SES compared to students of a low SES.…”
Section: Socioeconomic Status On the Relationship Between Teacher Sup...mentioning
confidence: 99%
“…Cemalcilar (2010) and Yue (2017) examined concepts related to teacher support (satisfaction with teacher-student relationships) and school belonging (depression) but not those factors specifically. This highlights the need for the current study to examine whether Cemalcilar's (2010) and Yue's (2017) results extend to perceived teacher support and sense of school belonging, which, if so, would result in the association between perceived teacher support and sense of school belonging being stronger for students of a high SES compared to students of a low SES. However, there is also literature that suggests teacher support can buffer the negative experiences students of a low SES tend to face (Berkowitz et al, 2016;Croninger & Lee, 2001).…”
Section: Socioeconomic Status On the Relationship Between Teacher Sup...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pengalaman positif berhubungan dengan: a) dukungan dan penerimaan dari guru dan teman sebaya berupa kehangatan dan kepercayaan serta adanya komunikasi yang terbuka, b) keterhubungan sekolah yang mengacu pada aspek keterlibatan, penghormatan, penghargaan, perhatian, serta dukungan kepada individu di sekolah (Stiglbauer et al, 2013;Yue, 2017;Moeller et al, 2020), dan c) penilaian yang adil (White et al, 2018). Sedangkan mengenai pengalaman sekolah negatif dengan merujuk dari beberapa hasil penelitian (Yue, 2017) mengkategorikannya dalam bentuk: a) perlakuan tidak adil oleh guru, b) penolakan teman sebaya, c) iklim disiplin yang rendah. Di pihak lain (UNICEF, 2006;Fauziati, 2016) menuliskan pengalaman negatif yang dialami anak di sekolah berupa ancaman hukuman, penghinaan, intimidasi, kekerasan fisik, psikologis, verbal, serta bentuk perundungan lainnya.…”
Section: Pendahuluanunclassified